Precipitação sazonal no Nordeste brasileiro: observada e simulada em anos de El Niño e de La Niña - LIMA, Helen Karollyne Lima de (2019)
A study of ratings generated by the model simulated precipitation RegCM4, using the parameterization GFC and MIT to reproduce the seasonal distribution of rainfall observed during summer / autumn of 1982 / 1983 (dry year) and 1988/1989 (rainy year) on the Northeast Brazil (NEB) using 30 km spatial resolution. Were used in this work 24 rounds corresponding to the seasonal rainfall in summer and autumn of the year, dry summer and rainy autumn of the year, with 12 rounds was used in the convective parameterization GFC related to the G1, G2 and G3 for two years ( La Niña and El Niño) and 12 rounds using the convective parameterization MIT, related to the G1, G2 and G3. In general these results indicate that simulations using the parameterization of RegCM4 GFC and MIT showed a systematic error of underestimation of precipitation in almost all regions of Northeastern Brazil. Since the simulation was that more was seen approaching the MIT, the field of grid G2.